Inputs and Outputs of R&D Activities of Enterprises in the Visegrad Group Countries - Martin, Marek (Wydawnictwo Politechniki Łódzkiej, 2025)
The aim of this study is to interpret and characterize the specific nature of R&D activities of enterprises in the Visegrad Group countries against the background of selected European Union economies. The study also attempts to assess the relationship between outputs and inputs generated by enterprises' R&D activities. The analyses used data from public statistics, particularly from Eurostat and the OECD, supplemented by publications and thematic reports. Due to the limitations of the volume of this study, the analyses conducted within this study utilized selected measures of R&D inputs and outputs of enterprises, as well as limited proposed indicators for measuring the relationship between outputs and inputs.
Keywords: Visegrad Group countries; enterprises; research; development; R&D measurements